Diagnostic abdominal MR imaging on a prototype low-field 0.55 T scanner operating at two different gradient strengths - Chandarana, Hersh; Bagga, Barun; Huang, Chenchan; Dane, Bari; Petrocelli, Robert; Bruno, Mary; Keerthivasan, Mahesh; Grodzki, David; Block, Kai Tobias; Stoffel, David; Sodickson, Daniel K. (Abdominal imaging, 2021)
Purpose To develop a protocol for abdominal imaging on a prototype 0.55 T scanner and to benchmark the image quality against conventional 1.5 T exam. Methods In this prospective IRB-approved HIPAA-compliant study, 10 healthy volunteers were recruited and imaged. A commercial MRI system was modified to operate at 0.55 T (LF) with two different gradient performance levels. Each subject underwent non-contrast abdominal examinations on the 0.55 T scanner utilizing higher gradients (LF-High), lower adjusted gradients (LF-Adjusted), and a conventional 1.5 T scanner. The following pulse sequences were optimized: fat-saturated T2-weighted imaging (T2WI), diffusion-weighted imaging (DWI), and Dixon T1-weighted imaging (T1WI). Three readers independently evaluated image quality in a blinded fashion on a 5-point Likert scale, with a score of 1 being non-diagnostic and 5 being excellent. An exact paired sample Wilcoxon signed-rank test was used to compare the image quality. Results Diagnostic image quality (overall image quality score ≥ 3) was achieved at LF in all subjects for T2WI, DWI, and T1WI with no more than one unit lower score than 1.5 T. The mean difference in overall image quality score was not significantly different between LF-High and LF-Adjusted for T2WI (95% CI − 0.44 to 0.44; p = 0.98), DWI (95% CI − 0.43 to 0.36; p = 0.92), and for T1 in- and out-of-phase imaging (95%C I − 0.36 to 0.27; p = 0.91) or T1 fat-sat (water only) images (95% CI − 0.24 to 0.18; p = 1.0). Conclusion Diagnostic abdominal MRI can be performed on a prototype 0.55 T scanner, either with conventional or with reduced gradient performance, within an acquisition time of 10 min or less.